KARAKTERISASI EKSTRAK KASAR LIPASE Rhizopus stolonifer UICC 137 - Sri Sumiarsih (The East Java Biological Society, 2001)
There is an increasing commercial interest in enzymatic production of biologically active component, because there are a number of well-known advantages compared to chemical synthesis. One of the most valuable synthetic features of enzyme is their ability to discriminate between enantiomers of racemic substrates. Lipase have become of great interest to the chemical industries wing their usefulness in both hydrolytic and synthesis reactions. The aim of this work was to study the production of lipase by Rhizopus stolonifer UICC 137, and determine the crude lipase preparation characteristics. The lipolytic activity was determined by titrimetric method toward oil-arabic gum emultion as a substrate. The strain produced lipase at appreciable lipolytic when cultivated for 72 hours in medium containing 3% glucose and 1% olive oil. Our data suggest that the strain produced lipase since the exponential phase of its growth. Lipase with optimum lipolytic activity was obtained at late stationary phase. The optimum condition for lipolytic activity measurement were pH of 7.5 and temperature 37oC, the crude enzyme had a specific activity 20.2 unit/ mg protein, the Vmax was 15.1 mol/ min and KM was 12.5 mg/ ml. The crude enzyme retained 79.9%, 68.0% and 52.6% of its lipolytic activity, when incubated for 90 minutes at temperature of 40, 50, and 60oC respectively.